Pengembangan Bahan Ajar Digital Berbasis Android untuk Peserta Didik Berkebutuhan Khusus - Safitri, Erna Retna; Nurkamilah, Siti (JOEAI (Journal of Education and Instruction), 2020)
This research generally aims to develop android-based teaching materials for students with special needs without intellectual barriers. The method used in this research is Research and Development (R&D). The development was carried out by adopting The Steps of System Approach Model of Educational Research and Development from Borg and Gall. The subjects and respondents in this study were students with special needs, teachers, parents and experts in the fields of learning, media and language. The results showed that digital teaching materials based on android can be developed. The results of expert judgement conducted by learning, media and language experts showed that the teaching materials developed are feasible to be used in learning for students with special needs with an average score of 3.7 that is categorized well. In conclusion, android-based teaching materials for students with special needs without intellectual barriers developed are feasible to use in the learning process. Keywords: Digital Teaching Materials, Android, Students with Special Needs